Penerapan Teori Betty Neuman dalam Pengkajian Lansia dengan Diabetes Mellitus di Desa Margalaksana Kecamatan Cilawu Kabupaten Garut - Luthfa, Iskim; Windani, M.S., Citra (Jurnal Keperawatan Komunitas, 2015)
Diabetes mellitus is a chronic disease that will suffer a lifetime. The impact will be felt by the patient and family care, even the community around him. This study aims to apply the theory of Betty Neuman in the assessment of elderly with diabetes in Margalaksana Village, District Garut. The design of this research is descriptive analytic, with a sample of 94 elderly people aged> 45 years. The results of the application of the theory of Betty Neuman in the assessment of elderly with diabetes, includes five aspects: developmental, physiological, psychological, socio-cultural and spiritual